Global Arms Production and Climate Change: Evaluating the Environmental Consequences of the Defense Industry - Dr. Syed Munib Ali Bukhari (Journal of Religion and Society, 2025)
The global defense industry, a colossal economic and political entity, is a significant yet often overlooked contributor to climate change. This article critically evaluates the environmental consequences of arms production and military operations, from carbon emissions and resource depletion to toxic waste and ecosystem degradation. By applying an analytical framework grounded in structural violence and ecological politics, the study dissects the systemic factors that enable the defense sector's environmental unaccountability. It reveals that the industry's massive carbon footprint, comparable to major industrial nations, is driven by a cycle of resource consumption and is largely shielded from international climate regulation. The paper argues for a fundamental reframing of security paradigms to integrate environmental accountability into defense strategies, thereby disrupting a self-perpetuating feedback loop where climate instability fuels militarization, which in turn exacerbates environmental degradation. Keywords: Defense Industry, Arms Production, Climate Change, Environmental Impact, Carbon Emissions, Sustainability